Effects of physical activity on brain function: Mechanisms, adaptations and clinical implications - Fabian, Dariusz; Kufel, Klaudia Maria; Teofilak, Mateusz; Smyl, Natalia Maria; Śpiołek, Olga; Siwiec, Jan; Słowikowska, Aleksandra; Szatkowska, Julia; Sztyler-Krąkowska, Marcelina Paula; Wąsowicz, Agnieszka Alicja; Kędziora, Franciszek (Quality in Sport, 2025)
The effects of physical activity on brain function, the mechanisms involved, adaptations, and clinical implications are topics of great importance given the increasingly common sedentary lifestyle. This paper explores these relationships, starting with the evolutionary aspects of brain development in the context of physical activity. It discusses a variety of forms of exercise, from intense exercise to daily NEAT (non-exercise activity thermogenesis). A key issue is neuroplasticity, which plays an important role in adaptation to external stimuli. The article identifies key neurotrophic factors, such as BDNF (brain-derived neurotrophic factor) and VEGF (vascular endothelial growth factor), which are regulated by physical activity and contribute to improved cognitive function and mental health. The paper demonstrates the multifaceted effects of physical activity on neuroplasticity and brain health.